Ethylene production by the potato tuber - Creech, David Lee, author; Workman, Milton, advisor; Hanan, Joe J., committee member; Harrison, Monty D., committee member; Moore, Frank D., III, committee member (Colorado State University. Libraries, 1971)
Russet Burbank tubers were stored at 32°F and 45°F and continuously ventilated with atmospheres of 2% O2, air, 80% O2, 4% CO2, 12% CO2, and intermittently ventilated with air. Ethylene production by the tubers was traced throughout a seven month storage period. Tubers stored in atmospheres of 2% O2, air, 4% CO2, and intermittent air at 32°F and 45°F evolved ethylene at a rate no greater than 0.008 ul kg-1 hr-1 throughout the storage period. In all cases where sprouting occurred, the rate of ethylene production increased. Tubers stored in 80% O2 and 12% CO2 succumbed to physiological breakdown and produced ethylene at rates much greater than the rates for tubers stored in the non-toxic atmospheres (2% O2, air, 4% CO2, and intermittent air). The peak rate of ethylene production observed was 0. 300 ul kg-1 hr-1 for tubers stored in 80% O2 at 45°F. In general, the higher temperature produced the higher rates of ethylene production. The only exception to this rule were those tubers stored in 12% CO2. Tubers inoculated with Alternaria solani and Fusarium roseum var. sambudnum were investigated for the ethylene-producing ability. Uninoculated tubers and tubers inoculated with Alternaria solani evolved ethylene at approximately the same rate. Tubers inoculated with Fusarium roseum, however, demonstrated greatly stimulated ethylene production, often as high as 0.100 ul kg-1 hr-1. Cultures of Fusarium roseum grown on PDA failed to produce ethylene.
Keywords: Potatoes